2005
DOI: 10.1086/431425
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in the Human Androgen Receptor Gene Is the Major Determinant of Common Early-Onset Androgenetic Alopecia

Abstract: Androgenetic alopecia (AGA), or male-pattern baldness, is the most common form of hair loss. Its pathogenesis is androgen dependent, and genetic predisposition is the major requirement for the phenotype. We demonstrate that genetic variability in the androgen receptor gene (AR) is the cardinal prerequisite for the development of early-onset AGA, with an etiological fraction of 0.46. The investigation of a large number of genetic variants covering the AR locus suggests that a polyglycine-encoding GGN repeat in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
143
3
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(164 citation statements)
references
References 40 publications
12
143
3
6
Order By: Relevance
“…In contrast to African population like Yoruba in Ibadan, Nigeria (YRI) showed the complete absence of wild homozygous genotype (T/T) and the presence of wild homozygous (C/C), but seems to be polymorphic in other African populations like Maasai in Kinyawa, Kenya (MKK) and African ancestry in Southwest USA (ASW) and European population like Utah residents with Northern and Western European ancestry from the CEPH collection (CEU). SNP rs5919393 (C/T) found to be associated with endometrial cancer [25], and androgenetic alopecia in European population [26]. However, SNP rs5919393 is found to be monomorphic in Chinese population [27] and in the present study (Table 2).…”
Section: Discussioncontrasting
confidence: 52%
“…In contrast to African population like Yoruba in Ibadan, Nigeria (YRI) showed the complete absence of wild homozygous genotype (T/T) and the presence of wild homozygous (C/C), but seems to be polymorphic in other African populations like Maasai in Kinyawa, Kenya (MKK) and African ancestry in Southwest USA (ASW) and European population like Utah residents with Northern and Western European ancestry from the CEPH collection (CEU). SNP rs5919393 (C/T) found to be associated with endometrial cancer [25], and androgenetic alopecia in European population [26]. However, SNP rs5919393 is found to be monomorphic in Chinese population [27] and in the present study (Table 2).…”
Section: Discussioncontrasting
confidence: 52%
“…An increased risk of prostate cancer has been associated with a short number (25,26) or high number (27) of GGN repeats. The most common allele has been reported to be correlated with androgenic baldness, while 24 GGN repeats seemed to have a protective role (13). Lower semen volumes were found in men with GGN lengths shorter than 23 (14).…”
Section: Discussionmentioning
confidence: 93%
“…Considerable discrepancies exist between the findings of the in vitro studies analyzing the effect of different GGN repeat lengths on AR activity in various cell cultures (7)(8)(9)(10)(11). Nevertheless, several epidemiological studies have suggested a significant, albeit modest, impact of the repeat on clinical androgenic effects; the GGN repeat has been linked to the risk of prostate cancer (12), to alopecia (13), spermatogenesis (14), occurrence of hypospadia (15), and breast cancer (16).…”
Section: Introductionmentioning
confidence: 99%
“…For instance the AR polymorphism, Stu 1 is prominently associated with AGA. 8 Additionally, the 5α-reductase, aromatase and estrogen receptor genes may contribute to occurrence of AGA. 9 Via the action of 5α-reductase, systemic testosterone is converted to dihydrotestosterone (DHT).…”
Section: 5mentioning
confidence: 99%